Physiological effects of acute intake of Irish blackcurrant juice during an incremental cycling test in endurance athletes - Byrne, G.; Murad, L.; Stewert, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
The polyphenol compound anthocyanin present in blackcurrant juice (BC) has been found to elicit positive biological action in terms of cardiovascular and metabolic functions. Supplementation of BC may also enhance aerobic exercise performance.